ETHNOLINGUISTIC PECULARITIES OF LEXICAL PARALLELS IN THE SPEECH OF NATIVE SPEAKERS OF THE DON AND UKRAINIAN SUBDIALECTS OF VOLGOGRAD REGION (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-3-93-105The speech of the indigenous inhabitant and emigrants, who came on the territories of later settlement, where Volgograd region belongs too (mostly its south-Russian provinces), abounds with the Ukrainian language units. The peculiarities of lexical parallels, reflecting the speech peculiarities of ethnic groups, who were representatives of the Don Сossaks and the Ukrainian emigrants or khokhol settlers, are under the analysis in the light of cultural and language specifics of the speech continuum in the settlements of the Don dialects in Volgograd region. The analysis has been carried out taking into consideration the accepted terms “dialect-speaker” and “Slavic language personality”. The article separates the correspondence of different levels of semantics and sense similarity: intralanguage (intradialect), interlanguage (interdialect) equivalents and analogues. This research also highlights the phenomena of iterdialect propertis and lexical filling of the language units. It brings to light theme attachment of the lexical parallels, defines common and specific options of their usage. It also defines the significancy of the correspondences in the native speakers’ speech as expressive means and a way to save this compiled language continuum of ethnocultural information of things of surrounding world, cooperative material and spiritual activities of ethnical settler’s groups in the places of their common dwelling.Key words: dialectology, ethnolinguistics, dialects of the Don and the Ukrainian regions, speech of dialect-speakers, lexical parallelsAcknowledgements: the study was supported by a grant from the Russian Science Foundation, project no. 23-28-01215, https://rscf.ru/project/23-28-01215/